Chemical castration in the criminal law system: A study of effectiveness and toxicological impact - Fitria, Yusian Eri; Vianto, Denny; Mashdurohatun, Anis; Wahyuningsih, Sri Endah; Hafidz, Jawade; Setiyawan, Deni (Edelweiss Applied Science and Technology, 2024)
Chemical castration is an additional punishment in Indonesia's criminal law system that is applied to sex offenders, especially against children, with the main objective of reducing recidivism rates and protecting the public from the threat of repeated sexual violence. However, this policy also raises various challenges and serious impacts, especially in the toxicology aspect. Medically, chemical castration can cause significant side effects, such as metabolic disorders, decreased bone density leading to osteoporosis, and the risk of cardiovascular disease. The purpose of this study is to examine the effectiveness of castration policy, the impact of castration from the toxicology aspect and policy recommendations for equitable chemical castration. This research uses normative juridical with statutory, case study and conceptual multidisciplinary approaches. The results of the study explain that chemical castration is legally effective, but the impact of castration implementation can cause several side effects for the perpetrator. A policy recommendation for chemical castration that is equitable is needed. This research can provide an overview of the implementation of chemical castration from the legal and toxicological aspects. So that the application of castration needs to be evaluated against toxicological and ethical impacts is very important to create a balance between the protection of society and respect for human rights. So as to create justice in the policy of chemical castration.